Rozwój controllingu z perspektywy doświadczeń naukowych ośrodków wrocławskich - Nowak, Edward (Cotrollership development from the perspective of academic experiences of Wroclaw academic centres, 2006)
The concept of controllership is widely accepted to be one of the most advanced and useful instrument in management which improves all managerial functions. The reason wh controllership is so important derives from the main focus of this instrument - to achieve objectives. This aim of this article is to present the research development and implementation works which have been started and are still continued by academic centres in Wroclaw.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 304-312